The The Evolution of Artificial Intelligence: A Comprehensive Analysis (Trinity Journal of Management, IT & Media (TJMITM), 2023)
In order to facilitate problem-solving, the discipline of artificial intelligence integrates computer science and substantial datasets. Additionally, it includes the branches of artificial intelligence known as deep learning and machine learning, which are frequently mentioned together. These fields use AI algorithms to build expert systems that make predictions or categorise information based on incoming data. Making intelligent machines, particularly intelligent computer programmes, is a scientific and engineering endeavour. Although it is related to the related task of using computers to understand human intelligence, AI need not be limited to techniques that can be observed through biological means.
Keywords: Artificial Intelligence; Decision making; Machine Learning; Problem solving algorithms; Evolution of AI